SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2017
DOI: 10.2118/186308-ms
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Influence of Nanoparticles on Rheological Properties of VES Fracturing Fluid

Abstract: The use of nanoparticles has been demonstrated to enhance the rheological properties of the viscoelastic surfactant (VES) fluid. However, their influence on the rheological properties as a function of temperature is not well known. In this study, a detailed analysis of improved rheological properties and thermal stability of the VES fluid beyond their optimal working temperature was conducted. The effect of nanoparticles was also studied. A base VES fluid was prepared with the required amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nasr-El-Din et al 2 MgO, ZnO Study of performance viscoelastic surfactant by adding nanoparticles Improving the rheological properties of fracturing fluid Gurluk 10 MgO, ZnO Growth of worm-like micelles at high temperature Addition of nanoparticles improves thermal stability and viscosity yield at different shear rates and temperature Aggarwal et al 157 nanocrystal Application of nanoparticles and hydrogel polymer technology to enhance fluid Use of nanotechnology can reduce requirement of VES fluid volume by 60%, permeability range of VES fluid is extended up to 2000 md. Sangaru et al 158 MgO, SiO 2 Improve rheological properties and thermal stability of VES Enhancement of low shear viscosities of VES with adding nanoparticles Ozden et al 159 MgO, ZnO Enhance the VES gel at 350 °F High durability of VES viscosity at 110 cP from 250 to 350 °F Chauhan et al 57 SiO 2 Effects of alkali on the viscosity, thermal stability, and miscibility of VES gel Mixed anionic−anionic system gives improved rheology compared to single anionic and mixed anionic-zwitterionic surfactant systems Wu et al 54 SiO…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Nasr-El-Din et al 2 MgO, ZnO Study of performance viscoelastic surfactant by adding nanoparticles Improving the rheological properties of fracturing fluid Gurluk 10 MgO, ZnO Growth of worm-like micelles at high temperature Addition of nanoparticles improves thermal stability and viscosity yield at different shear rates and temperature Aggarwal et al 157 nanocrystal Application of nanoparticles and hydrogel polymer technology to enhance fluid Use of nanotechnology can reduce requirement of VES fluid volume by 60%, permeability range of VES fluid is extended up to 2000 md. Sangaru et al 158 MgO, SiO 2 Improve rheological properties and thermal stability of VES Enhancement of low shear viscosities of VES with adding nanoparticles Ozden et al 159 MgO, ZnO Enhance the VES gel at 350 °F High durability of VES viscosity at 110 cP from 250 to 350 °F Chauhan et al 57 SiO 2 Effects of alkali on the viscosity, thermal stability, and miscibility of VES gel Mixed anionic−anionic system gives improved rheology compared to single anionic and mixed anionic-zwitterionic surfactant systems Wu et al 54 SiO…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Sangaru et al. showed that the addition of NPs to the VES solution prepared in concentrated seawater (total dissolved solids of 63 000 ppm) resulted in a noticeable increase for the apparent viscosity at shear rates less than 10 s –1 . , The experiments were conducted at 300 °F and 500 psi. The apparent viscosity increased almost 4-fold after the addition of NPs.…”
Section: Application Of Nps In Surfactant and Polymer-based Stimulationmentioning
confidence: 99%
“…Due to the instability of VES fracturing fluid under high temperature, high pressure, and high shear rate, some researchers have aimed to significantly improve the temperature and shear resistance of VES fracturing fluids, reduce the fluid loss of VES fracturing fluids, and further enhance the sand-carrying performance of VES fracturing fluids by combining nanomaterials with VES fracturing fluids to take advantage the unique physical and chemical properties of nanomaterials. Hanafy et al have investigated the effects of the shape, size, and surface properties of nanoparticles on the micellization and cross-linking process of anionic VES fracturing fluid. It was found that the addition of spherical or rod-shaped silica nanoparticles to 4 wt % in an anionic VES system can increase the apparent viscosity by 50% at 280 °F.…”
Section: Application Of Nanotechnology In Hydraulic Fracturing Of Unc...mentioning
confidence: 99%